Entitas Budaya Minangkabau dan Kearifan Lokal dalam Film Dokumenter Transformasi Bentuk Wayang Kulit Sawahlunto - Sasongko, Hery; Fitri, Diniya; Putra, Gilang Febriano (Sense: Journal of Film and Television Studies, 2024)
The production of the documentary film Transformation of the Sawahlunto shadow puppet form aims to be a reference material both for learning and awareness and in archive form as well as presenting an entertaining and educational presentation. The creation method applies stages and procedures in the television program production process consisting of Development, preproduction, production, post production. Arranged in a logical order, from simple to increasingly complex, from light to heavy. Also think about refreshing elements to make the film interesting. This film tells the story of the existence of Sawahlunto shadow puppets whose characters and forms are inspired by the historical story of coal mining and all the life that accompanies it due to the fact that workers were brought in from outside the area, thus indirectly fostering a new culture in Sawahlunto. However, this does not necessarily eliminate local culture, they go hand in hand which in the end actually becomes a strength. Philosophically, the story is expressed in the characters and forms of the Sawalunto shadow puppets. It is very important to prepare the production of a mature documentary film in the pre-production stage, during research it is best to approach the environment that will be used as the production location first. One thing that must be remembered is that when conducting research and selecting sources, it must be based on track records with the aim of getting a lot of accurate information to further strengthen the content of the story that will be built in the documentary film.